Doutores Só Risos: percepção dos estudantes sobre as contribuições da palhaçaria na sua formação médica - Resende, Mylvia David Chiaradia de (2020)
“Health Services Humanization” is presently a very recurrent topic. According to 2014 Brazilian National Curricular Guidelines, the educational model for Medical Schools should aim toward a more humane, critical and thoughtful professional. Some institutions include in their curricula complementary actions using arts so as to sensitize students. In this scenario, clowning stands out, performed in philanthropic institutions and hospitals by students from various health-related arias, based on models performed by professional and voluntary artists. Aims: to assess the effect of the experience with clowning in the lives of medical students and identify changes in their personal and academic lives. Materials and methods: Qualitative and phenomenological studies, performed by means of semi-structured interviews and non-participating direct observation, with medical students taking part of the Doutores Só Risos (“All-Laughter Doctors”) extension project of Universidade José do Rosário Vellano, in Belo Horizonte, state of Minas Gerais, southeastern Brazil. 13 volunteers were chosen as samples. The data had their contents analyzed using Bardin’s proposed categorization. All volunteers signed an Informed Free Consent Term before their inclusion in the project. Results: students showed great interest in clowning, as they saw in this activity an opportunity to help people face a vulnerability situation, such as illness or social problem, bringing joy and comfort to such patients. Another noteworthy result pointed toward clowning allowing a precocious contact with committed patients, as this contact during medical studies normally comes at a later stage. Clowning also brought about changes in students’ lives, as it helped them improve their communication styles, in addition to overcoming shyness. They also stated they valued life itself more after experiencing problems from realities differing from their own. Regarding the undergraduate curriculum, students showed improvement in their relation towards patients, as they started listening more, improving empathy, as they then began to see the other, i.e., the patient, inside a whole biopsychosocial aspect. Conclusions: Inserting activities connected to arts, focusing on clowning, presented great potential to bring about changes in attitudes and behaviors for medical students, contributing also to develop necessary competences for a more humane medical care